Why geography matters three challenges facing America : climate change, the rise of China, and global terrorism - De Blij, Harm J. (Oxford University Press, 2007)
Demonstrates how geography's perspectives yield unique and penetrating insights into the interconnections that mark our shrinking world. This book shows how and why the US has become the world's most geographically illiterate society of consequence - and demonstrates that this geographic illiteracy is a direct risk to America's national security.